Child Crime As Perpetrators Of Immoral Crimes - Zulfikar Kamarmir; Junifer Dame Panjaitan (International Journal of Social Research, 2023)
This research delves into the criminal responsibility of children engaged in moral crimes, specifically focusing on decency crimes like rape within the framework of Indonesia's legal system, as outlined in "Law Number 11 of 2012 concerning the Juvenile Criminal Justice System." Employing a normative juridical approach, the study analyzes legal statutes and cases related to such crimes, revealing a discrepancy between existing laws and their implementation. Instances of lenient sentencing, such as a six-month term for a severe crime, underscore the need for a closer examination of the diversion approach to reduce decency crimes by children. The research explores the concept of effective punishment within the unique context of juvenile offenders, advocating for the Juvenile Criminal Justice System's role in social rehabilitation through institutions like the Special Child Development Institute. Despite legislative efforts, inconsistencies persist, highlighting the necessity for a more stringent application of legal rules and a commitment to children's rights during the criminal justice process. Ultimately, the study emphasizes the importance of aligning punishment with juvenile characteristics, urging a shift towards comprehensive measures that promote personal growth and responsibility. It underscores the significance of upholding children's rights while addressing societal concerns related to reducing moral crimes committed by children through rigorous legal implementation.